2008
DOI: 10.1021/jp807904s
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Plasmonic Nanoparticle Pairs As a Plasmon Ruler: The Dependence of the Near-Field Dipole Plasmon Coupling on Nanoparticle Size and Shape

Abstract: The localized surface plasmon resonance (LSPR) spectral band of a gold or silver nanoparticle is observed to shift as a result of the near-field plasmonic field of another nanoparticle. The dependence of the observed shift on the interparticle distance is used as a ruler in biological systems and gave rise to a plasmonic ruler equation in which the fractional shift in the dipole resonance is found to decrease near exponentially with the interparticle separation in units of the particle size. The exponential de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
223
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(235 citation statements)
references
References 42 publications
12
223
0
Order By: Relevance
“…Similar observations were also reported by Ananth [6] and Mbhele [17]. The red-shift phenomenon of the LSPR Ag-NPs was simply can examined by scattering [18]. Increasing the particle size will increase the scattering process and the external driving field becomes non uniform across each particle.…”
Section: Methodssupporting
confidence: 81%
“…Similar observations were also reported by Ananth [6] and Mbhele [17]. The red-shift phenomenon of the LSPR Ag-NPs was simply can examined by scattering [18]. Increasing the particle size will increase the scattering process and the external driving field becomes non uniform across each particle.…”
Section: Methodssupporting
confidence: 81%
“…If a universal scaling law exists then interparticle distances can be measured to nanometer resolution by simply measuring the mode shift. In some papers [2,5] it has been suggested that mode shifting due to two arbitrary particles is universally exponential, however other experimental and numerical results for coupled gold rods [6] implied a different relationship, as have other studies. We shall now summarize some relevant investigations of linear chain of n spheres, including the special bisphere or dimer case where n = 2.…”
Section: Introductionmentioning
confidence: 89%
“…In particular, it has been suggested that the mode shifting could be employed as a nanometric ruler [2,5], by relating the position of the mode to the gap between particles. If a universal scaling law exists then interparticle distances can be measured to nanometer resolution by simply measuring the mode shift.…”
Section: Introductionmentioning
confidence: 99%
“…Electron-phonon coupling efficiency can be described in part by the coupling constant g and is known to increase linearly with increasing S/V ratio [148,149,[178][179][180][181][182].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 99%